Tympanic Resonance Hypothesis - Boedts, Michael J. O. (Frontiers in Neurology, 2020)
Seemingly unrelated symptoms in the head and neck region are eliminated when a patch is applied on specific locations on the Tympanic Membrane. Clinically, two distinct patient populations can be distinguished; cervical and masticatory muscle tensions are involved, and mental moods of anxiety or need. Clinical observations lead to the hypothesis of a “Tympanic Resonance Regulating System”. Its controller, the Brainstem Attention Centre, integrates external auditory, somatosensory and central impulses. It modulates auditory attention, and directs it toward unpredictable external or expected domestic and internal sounds: peripherally by shifting the resonance frequencies of the Tympanic Membrane; centrally by influencing the troughput of auditory information to the neural attention networks that toggle between scanning and focussing; and thus altering the perception of auditory information. ‘Tympanic Dissonance’ results in a host of local and distant symptoms, most of which can be attributed to activation of the Brainstem Attention Centre. Diagnostic and therapeutic measures for this ‘Tympanic Dissonance Syndrome’ are suggested.